(0,-3) see attached graph
a. to solve the system, graph the two equations.
x = y+3 becomes y=x-3 has m=1/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move up 1 unit and 1 unit to the right. plot a point and connect.
y=-4x+3 has m =-4/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move down four units and to the right 1 unit. plot a point and connect.
the solution is the point (x,y) where the two lines intersect. by the graph below it is (0,-3).
b. to solve by substitution, substitute y = -4x-3 into x= y+3
x= (-4x-3) +3
now substitute x = 0 back in to find y.
solution is (0,-3)
c. use elimination by adding the equations together.
then substitute into one equation to find y.
add an image